Speech by Brig. Jen. Datuk Prof. Dr. Kamarudin Hussin at the Soil Science Conference of Malaysia 2014 - Kamarudin, Hussin, Brig. Jen. Datuk Prof. Dr. (Universiti Malaysia Perlis, 2015)
Ceremony at the Putra Palace Hotel, Perlis.